(untitled) (CIPEEX, 2025)
Total hip arthroplasty (THA) is widely used to treat chronic refractory pain and conditions such as osteoarthritis, rheumatoid arthritis, fractures, and avascular necrosis. The procedure replaces the hip joint with a prosthesis, offering significant pain relief and improving function. Several surgical approaches are available, with anterior, posterior, and lateral techniques being the most common. The choice of the ideal approach is still debated, but the lateral approach, proposed by Hardinge, is valued for its excellent exposure of the joint and lower risk of prosthesis dislocation, despite disadvantages such as possible claudication due to a release of the gluteal tendon. This study reviews the quality of life of patients subjected to THA using the WOMAC questionnaire, which assesses pain, stiffness, and physical function. Analyzing three recent clinical studies, it was observed that most patients had a positive recovery, with a high prosthesis survival rate and significant improvements in WOMAC scores. The use of complementary tools such as AVIP showed additional benefits, such as reduced anxiety and improved mobility. The results highlight the effectiveness of hip arthroplasty and the importance of WOMAC for monitoring patient recovery and quality of life.